Enhanced immunogenicity of HIV-1 vaccine construct by modification of the native peptide sequence - Ahlers, Jeffrey D. (National Academy of Sciences, 1997)
Viral proteins are not naturally selected for high affinity major histocompatibility complex (MHC) binding sequences; indeed, if there is any selection, it is likely to be negative in nature. Thus, one should be able to increase viral peptide binding to MHC in the rational design of synthetic peptide vaccines. The T1 helper peptide from the HIV-1 envelope protein was made more immunogenic for inducing T cell proliferation to the native sequence by replacing a residue that exerts an adverse influence on peptide binding to an MHC class II molecule. Mice immunized with vaccine constructs combining the more potent Th helper (Th) epitope with a cytotoxic T lymphocyte (CTL) determinant developed greatly enhanced CTL responses. Use of class II MHC-congenic mice confirmed that the enhancement of CTL response was due to class II-restricted help. Thus, enhanced T cell help is key for optimal induction of CTL, and, by modification of the native immunogen to increase binding to MHC, it is possible to develop second generation vaccine constructs that enhance both Th cell activation and CTL induction.